2021
DOI: 10.3390/ph14040326
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline: A Candidate for Adjunct Treatment of Multiple Sclerosis

Abstract: In remitting–relapsing multiple sclerosis (RR-MS), relapses are driven by autoreactive immune cells that enter the brain and spinal cord and damage myelin sheaths of axons in white and grey matter, whereas during remissions myelin is repaired by activated oligodendroglial cells. Disease-modifying therapies (DMTs) may either retard/attenuate myelin damage or promote/enhance/speed up myelin repair. Almost all currently approved DMTs inhibit myelin damage and are considerably toxic. Enhancement of myelin repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Citicoline, a neuroprotective drug, has been shown to improve and speed up remyelination in MS patients. It was found to be significantly effective in two complementary MS rodent models [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citicoline, a neuroprotective drug, has been shown to improve and speed up remyelination in MS patients. It was found to be significantly effective in two complementary MS rodent models [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While our study analyzed only the neuroprotective efficacy of citicoline among patients following TBI, clinical trials and real-life studies have confirmed its excellent safety profile [ 5 , 14 , 17 ]. The neuroprotective effects of citicoline should not be limited to patients with TBI but instead could also be extended to patients with other neurological diseases [ 14 ], as some studies have suggested, including COVID-19-related cognitive complications, multiple sclerosis, and dementia [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioavailability of CDP-choline administrated upon oral and intravenous routes is similar [75]. After injection, CDP-choline is rapidly metabolized to its cholinergic and pyrimidinergic catabolites, being probably even safer and a more "procognitive" form of choline supplement [76][77][78][79][80][81]. Nevertheless, there are still a lot of open questions regarding the place and particular mechanisms of CDP-choline catabolism and its precise mode of action as well its involvement in some kinases activation and trimethylamine N-oxide (TMAO) formation [58,76].…”
Section: Discussionmentioning
confidence: 99%